STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI ERA DIGITALISASI - Edison Rumbiak; Petrus Irianto; Robert Masreng; Ida M. Hutabarat; Yulius Mataputun; Diki Kurniawan (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
This research aims to analyze the principal's leadership strategies in improving teacher performance in the digitalization era at SMP Negeri 2 Tiom, Lanny Jaya Regency, Highland Papua Province. The focus includes strategies for fostering morale and confidence, providing guidance and direction, the role of modeling, and providing inspiration, as well as identifying supporting factors, inhibitors, and the impact of these strategies. This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews with eight informants (principal, teachers, operator, committee, and students), participant observation, and documentation studies. Data analysis was conducted using the Miles and Huberman interactive model, consisting of data condensation, data display, and conclusion drawing. The results indicate that the principal implements a "Context-Responsive Digital Leadership" strategy through a humanist and communicative approach to reduce the psychological barriers of teachers in 3T (Frontier, Outermost, and Disadvantaged) regions. Guidance is provided through reflective clinical supervision and internal peer mentoring programs to overcome the limitations of external training. The principal's digital role modeling in school administration serves as a catalyst for teachers to begin adopting technology gradually. The findings identify that the availability of 24-hour electricity since mid-2024 is a primary supporting factor, while internet infrastructure and the 2026 student device restriction policy are significant inhibitors. The implementation of these strategies has a positive impact on increasing teacher discipline and student learning motivation. The study concludes that integrating "Noken" local wisdom values into the school's digital culture strengthens the resilience of educational institutions in remote areas.